2011
DOI: 10.1016/j.radmeas.2011.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a novel radiophotoluminescent readout system using a cw modulated UV laser diode and phase-sensitive technique

Abstract: We have proposed and constructed a novel readout system for measuring a dose-dependent radiophotoluminescence (RPL) signal of a silver-activated phosphate glass dosimeter. The present reader consists of a modulated continuous-wave (cw) ultraviolet (UV)laser diode at 375 nm as an excitation and a phase-sensitive technique using a lock-in amplifier. Preliminary results using a home-made reader are compared with those of the conventional technique based on a combination of a pulsed UV N 2 laser excitation at 337 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Aromatic cyanate ester resins have emerged as a new class of thermosets for use in the aerospace and electronics industry. 25,26 Compared to epoxies, they are thermally more stable, and have significantly better electrical properties. Cyanate esters also offer ease of handling and processing similar to that of epoxy resin systems.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic cyanate ester resins have emerged as a new class of thermosets for use in the aerospace and electronics industry. 25,26 Compared to epoxies, they are thermally more stable, and have significantly better electrical properties. Cyanate esters also offer ease of handling and processing similar to that of epoxy resin systems.…”
Section: Introductionmentioning
confidence: 99%
“…As already reported (Kurobori et al, 2010), the former peak at 310 nm was attributed to the Ag 2+ centers, while the latter peaks at 270 and 345 nm were attributed to Ag 2 + and Ag 0 centers, respectively. Therefore, in this work, the blue emission due to the Ag 0 centers and some portion of the orange emission due to the Ag 2+ centers were simultaneously emitted by an excitation wavelength of 375 nm from the laser diode (Zhao et al, 2011). Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The emission spectra of the RPL(Cu) phosphate glass dosimeter were measured using a photoluminescence (PL) spectroscopy and imaging system (UVR-260-SO, Seishin Corp.) with a UV-VIS spectrometer (iHR320, Horiba Ltd.)]. We expected that the RPL emission from the silver activator would have a broad peak with two emission bands related to Ag 0 and Ag 2+ , as was previously observed at about 635 nm with excitation by UV laser of wavelength 365 nm [13,17,18] . Previous studies have shown that the RPL excitation spectrum consists of two excitation bands peaking at about 315 nm (3.93 eV) and 373 nm (3.32 eV) [19] .…”
Section: C) Measurement Apparatus For Radio-photoluminescence From Ph...mentioning
confidence: 99%